Why is primary hyperparathyroidism more severe in children?. (February 2021) - McKenna, Kelly; Dunbar, Nancy Street; Parham, Kourosh
Abstract: The disease presentation of primary hyperparathyroidism (PHPT) is more severe in children. We hypothesize that this difference in disease presentation is a result of several factors including a delay in diagnosis, age-related differences in calcium metabolism and bone turnover, and the influence of the growth hormone (GH)/insulin growth factor-1 (IGF-1) axis. Only the first two explanations for the heightened disease severity of PHPT in children have been previously discussed in the literature. In regards to the potential role GH and IGF-1 may play in this disparity, previous studies have documented decreases in GH and IGF-1 secretion in symptomatic adult PHPT patients potentially influencing the severity of the patients' disease presentation. While these studies have yet to be replicated in the pediatric population, given that both GH and IGF-1 are important for the achievement of peak bone mass in young individuals, it is logical to infer that the GH/IGF-1 axis may be partly responsible for the severe presentation of PHPT in children.